Tuning Charge Carrier Dynamics and Surface Passivation in Organolead Halide Perovskites with Capping Ligands and Metal Oxide Interfaces - James Durrant (Advanced Optical Materials, 2018)
Organolead halide perovskites have emerged as exciting optoelectronic materials but a complete understanding of their photophysical properties is still lacking. Here, a morphological series of methylammonium lead bromide (MAPbBr3) perovskites are studied by transient optical spectroscopies over eight orders of magnitude in timescale to investigate the effect of nanostructuring and surface states on the charge carrier dynamics. The sample preparation route and corresponding morphology changes influence the position of the optical features, recombination dynamics, excitation fluence dependence, and dramatically impact surface trap passivation. Growth of the perovskite layer in the presence of capping ligands or within mesoporous alumina increases the photoluminescence efficiency by multiple orders of magnitude, indicating that interfacing with metal oxides can lead to the passivation of surface nonradiative recombination centers. Nanoparticles (NPs) dispersed in solution show mixed behavior since they consist of NPs on nanoplatelets, while isolated NPs could be grown within mesoporous alumina with the addition of capping ligands. Investigation on the microsecond timescale suggests that an exponential distribution of states below the band edges results in long-lived charges. The investigations of the relationship between sample architecture and charge carrier dynamics will help in the appropriate choice of perovskite morphology for use in optoelectronic devices.